Shiga Toxin-Producing Escherichia Coli Isolated From Lettuce Samples in Tehran, Iran - Mazaheri, Somayeh (Jundishapur J Microbiol, 2014)
BACKGROUND: During the last decade, the prevalence of foodborne diseases due to contaminated food as well as the outbreaks of diseases due to Shiga toxin-producing Escherichia coli (STEC) strains has increased. OBJECTIVES: The aim of this study was to evaluate the prevalence and antibiotic resistance pattern of STEC strains in lettuce samples. Since lettuce is used as a raw vegetable in salads, the rates of infections caused by this vegetable are high. MATERIALS AND METHODS: A total of 100 samples collected from Tehran, Iran, were transported to the laboratory, homogenized by a stomacher in E. coli broth containing cefixime, and cultured on MacConkey agar medium. Their DNA was extracted by boiling method and polymerase chain reaction (PCR) was performed, using five primers targeting the stx1, stx2, fliCh7, rbfO157, and eaeA genes. Susceptibility testing against ampicillin, imipenem, cephalosporin, tetracycline, aminoglycosides, chloramphenicol and quinolones was performed using disk diffusion method. RESULTS: Eight samples were positive for presence of STEC strains, three contained stx1, five contained stx2, and one sample was positive for presence of both rbfO157 and fliCh7. They were susceptible to all the antibiotics except for ampicillin and tetracycline. CONCLUSIONS: This study indicated the contamination of lettuce by STEC strains and its possible role as the source of infection. Resistance to both tetracycline and ampicillin may be considered as an emergency alarm for a multidrug resistance of STEC strains.